2019
DOI: 10.1017/s2040174419000631
|View full text |Cite
|
Sign up to set email alerts
|

Birth size and cancer prognosis: a systematic review and meta-analysis

Abstract: AbstractThere is an established link between birth parameters and risk of adult-onset cancers. The Developmental Origins of Health and Disease concept provides potential underlying mechanisms for such associations, including intrauterine exposure to endogenous hormones (androgens and estrogens), insulin-like growth factors, etc. However, there is conflicting evidence on the association between birth parameters and the cancer mortality risk. Therefore, we aimed to review and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, birth size has been also shown to be positively related with estradiol level in adulthood [18,32,33]. Birth weight was also found to be positively related with breast cancer risk in women ( [2,15,26,52]; however see for contradictory results: [70]). The suggested mechanism for this is life-time exposure to high levels of estradiol [60].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, birth size has been also shown to be positively related with estradiol level in adulthood [18,32,33]. Birth weight was also found to be positively related with breast cancer risk in women ( [2,15,26,52]; however see for contradictory results: [70]). The suggested mechanism for this is life-time exposure to high levels of estradiol [60].…”
Section: Introductionmentioning
confidence: 99%
“…It appears that being active helps to control low birth weight [ 67 ] and reduces the risk of macrosomia by up to 30% [ 41 ]. Both birth weight extremes are negatively associated with the development of the infant in the short and long term [ 68 , 69 , 70 , 71 , 72 ]. Less than half of the NICU admissions (a proxy for newborn health) were found in the IG (n = 9) compared to the CG (n = 20), with percentages for the total group being 13% vs. 29% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis on the association of BW and cancer mortality by Risnes et al [ 44 ] showed that BW in men was positively associated with cancer mortality, whereas in women there was no strong evidence. Later, a meta-analysis by Sharma et al [ 52 ] found conflicting results, with BW associated with the poorer prognosis of some cancers (prostate) but not others (breast). However, this aspect was not investigated in our study.…”
Section: Discussionmentioning
confidence: 99%